The mediating role of key audit matters readability on the effect of auditor personality on investor reaction - Herina, Herina; Setijaningsih, Herlin Tundjung; Widuri, Rindang (Edelweiss Applied Science and Technology, 2025)
This study examines the effect of auditor personality, especially narcissism and confidence, on investor reaction mediated by Key Audit Matters (KAM) readability in emerging market. We focused on firms listed in the Kompas 100 index on the Indonesia Stock Exchange during the 2022-2023 period. With Stata software support, we used path analysis with Structural Equation Modeling (SEM). The findings indicate that auditor narcissism has a significant positive effect on KAM readability, while auditor confidence has a significant negative effect. Furthermore, it was found that KAM readability has a significant negative effect on investor reaction. It significantly mediates the effect of auditor narcissism on investor reaction, indicating that while narcissistic auditors improve KAM readability, this clarity enables investors to identify company risks, potentially triggering negative market reactions. However, despite showing a positive relationship, KAM readability does not successfully mediate the effect of auditor confidence on investor reaction. The conclusion of this study underscores the significance of auditors presenting clear and understandable information and the impact of auditor personality traits on KAM disclosures and market responses. This study is expected to offer valuable insights for auditors to enhance disclosure practices and help investors make better decisions.